Sustainable lightweight composite materials - Maleque, Md. Abdul; Halim, Zahurin; Ahmad Azhar, Ahmad Zahirani; Mohd Zaki, Hafizah Hanim; A.R., Nur Farina; Parveez, Bisma (2019)
The novelty of this invention is to use eco-SiC from agricultural waste rice husk as reinforcement for sustainable composite materials development with the aim to reduce weight, enhance energy efficiency and save fuel consumption of motorbike. Developed by simple and cost effective green production technique of powder metallurgy, reducing hazardous CO2 gas compared to cast iron casting production.